Interleukin 2 and interferon-gamma augment anticolon antibody dependent cellular cytotoxicity in ulcerative colitis. Issue 6 (June 1993) - Hibi, T; Ohara, M; Watanabe, M; Kanai, T; Takaishi, H; Hayashi, A; Hosoda, Y; Ogata, H; Iwao, Y; Aiso, S
Abstract : In vitro effects of cytokines and therapeutic drugs on antibody dependent cellular cytotoxicity (ADCC) mediated by anticolon antibody were investigated in serum samples from patients with ulcerative colitis. A 51Cr release assay was used to examine ADCC activity with the colon cancer cell line, colo 205, as the target and peripheral blood mononuclear cells as the effector. High ADCC activity was shown in 13 of 32 (41%) patients with ulcerative colitis. This ADCC activity was inhibited by protein A treatment of the serum samples. Interleukin 2 (IL2) activated effector cells could enhance ADCC activity, but interferon-gamma (IFN-gamma) or tumour necrosis factor-alpha (TNF-alpha) had no effect on the cytotoxic activity of effector cells. Treatment of target cells with IFN-gamma increased the vulnerability of these cells to ADCC with a large increase of intercellular adhesion molecule-1 (ICAM-1) expression on their surface. Monoclonal antibodies to ICAM-1 inhibited this IFN-gamma enhanced ADCC activity. Interestingly, prednisolone (PSL) reduced ADCC activity, but sulphasalazine (SASP) or 5-aminosalicylic acid (5-ASA) did not. These results suggest that IL2 and IFN-gamma could enhance colonic epithelial cell injury mediated by the ADCC mechanism in ulcerative colitis and that ADCC enhanced by cytokines is restored by PSL treatment.